2017
DOI: 10.1128/cmr.00120-16
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antibiotics in Modulating Virulence in Staphylococcus aureus

Abstract: is often involved in severe infections, in which the effects of bacterial virulence factors have great importance. Antistaphylococcal regimens should take into account the different effects of antibacterial agents on the expression of virulence factors and on the host's immune response. A PubMed literature search was performed to select relevant articles on the effects of antibiotics on staphylococcal toxin production and on the host immune response. Information was sorted according to the methods used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 169 publications
(356 reference statements)
7
94
1
Order By: Relevance
“…It is reported that the subinhibitory concentrations of β-lactam antibiotics can induce the production of some S. aureus toxins, such as alpha-toxin [12], PVL [2], and enterotoxins [13], or immune evasion molecules, such as SPA [14]. Here, S. aureus N315, which is a globally prevalent sequence type 5 (ST5) MRSA strain [21], was tested for its antibiotic response to identify new factors contributing to MRSA pathogenesis in antibiotic induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the subinhibitory concentrations of β-lactam antibiotics can induce the production of some S. aureus toxins, such as alpha-toxin [12], PVL [2], and enterotoxins [13], or immune evasion molecules, such as SPA [14]. Here, S. aureus N315, which is a globally prevalent sequence type 5 (ST5) MRSA strain [21], was tested for its antibiotic response to identify new factors contributing to MRSA pathogenesis in antibiotic induction.…”
Section: Resultsmentioning
confidence: 99%
“…β-lactams as antibiotics block the cell wall synthesis of bacteria to exert antimicrobial effects. By contrast, β-lactams as inductors may trigger global regulatory networks to modulate virulence in S. aureus [13]. RT-qPCR revealed that the expression of global regulators, including sarA, agrA, RNAIII, rot, ccpA, and saeR , increased in OXA-treated N315 compared with those in the untreated ones (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics may, therefore, inhibit some detrimental effects of infection without necessarily reducing the bacterial burden. Indeed, subinhibitory concentrations of antibiotics modulate the expression of global virulence loci in S. aureus (i.e., SarA , Sae , and Agr ) . The resulting changes in the profile of secreted virulence factors may lead to a reduced impact on tissue degradation or cell cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subinhibitory concentrations of antibiotics modulate the expression of global virulence loci in S. aureus (i.e., SarA, Sae, and Agr). 111 The resulting changes in the profile of secreted virulence factors may lead to a reduced impact on tissue degradation or cell cytotoxicity. 40,112,113 Alternatively, it is possible that antibiotics initially reduce the bacterial burden, allowing bone healing to be initiated before the infection reactivates.…”
Section: What Is the Mechanism Of The Observed Pro-osteogenic Responsmentioning
confidence: 99%